Enzymatic hydrolysate of geniposide directly acts as cross-linking agent for enzyme immobilization. (December 2020) - Ouyang, Jie; Pu, Shujin; Wang, Juzheng; Deng, Yuefeng; Yang, Chengli; Naseer, Sidra; Li, Dali
Graphical abstract: Highlights: The chitosan@β-glucosidase was used to hydrolyze natural product geniposide. Enzymatic hydrolysate of geniposide as cross-linking agent directly immobilized laccase. The Nano-SiO2 @laccase has excellent enzymatic properties and great reusability. Abstract: Enzyme immobilization is a routine biotechnology of many industries such as pharmaceutical, chemical and food. Among the different techniques of enzyme immobilization, cross-linking methods are often used. Geniposide is a natural product extracted from gardenia and its hydrolysate genipin is one of green cross-linking agent for enzyme immobilization, but the environmental pollution and cost of the genipin extraction process have become the main obstacle to its wide application. Enzyme β-glucosidase was immobilized on chitosan by self-catalysis and further used to hydrolyze geniposide. The laccase was immobilized on Nano-SiO2 through the hydrolysate of geniposide directly acts as cross-linking agent. The simplification of the extraction steps overcomes the obstacles to the widespread use of genipin. Compared with the free laccase, the Nano-SiO2 @laccase exhibited better pH stability and thermal stability. The Nano-SiO2 @laccase was used to degrade Bisphenol A (BPA) and the biodegradation efficiency of the Nano-SiO2 @laccase was 84.3 % after 10 cycles of reusing.